Relevance of QS. Ali 'Imran [3]: 8 from Carl Rogers' Humanistic Perspective to the Psychological Well-Being of Islamic Boarding School Students: A Systematic Literature Review - Arzak Mahardika; Aria Panji Saputra (Lembaga Bale Literasi, 2026)
The mental health of pesantren students is a crucial aspect of the educational process at Islamic boarding schools, as it relates to an individual’s ability to manage emotions, cope with stress, and develop a well-balanced personality. Surah ?li ‘Imr?n [3]: 8 conveys the values of steadfastness, a plea for guidance, and hope for the mercy of Allah SWT, all of which are relevant to strengthening an individual’s psychological well-being. This study aims to analyze the relevance of QS. ?li ‘Imr?n [3]: 8 to the psychological well-being of Islamic boarding school students through the lens of Carl Rogers’ humanistic psychology. This study employs a qualitative method using the Systematic Literature Review (SLR) approach by analyzing 15 relevant peer-reviewed articles indexed in reputable databases. Research data were obtained through the review and analysis of various scientific literature related to the values of the Qur’an, mental health, Islamic boarding school education, and Carl Rogers’ humanistic psychology theory. The results of the study indicate that the values in QS. ?li ‘Imr?n [3]: 8 contribute to strengthening the mental resilience of santri by fostering self-resilience, emotional stability, and a positive self-concept. From Carl Rogers’ perspective, these values relate to self-concept, congruence, self-acceptance, and the actualization of individual potential. Thus, the integration of Qur’anic values and humanistic psychology can serve as an approach to supporting the psychological well-being of Islamic boarding school students.